(untitled) (American Journal of Islam and Society, 2025)
Islamic law, its classical origins and modern resurgence, has been the subject of increasing attention in academia. Whereas previous literature in the area of Islamic law often carried orientalist leanings, modern research attempts to re-evaluate the Islamic legal tradition on its own merits. Dr. Omer Awass contributes to this effort in, Fatwa and the Making and Renewal of Islamic Law: From the Classical Period to the Present. Awass examines the formation, history, and transformation of Islamic legal discourse and institutions through the lens of the fatwa, or legal opinion. He explores how the issuing of fatwas was influential in the development of the legal tradition generally, while at the same time serving as a social instrument that contributed to the formation of the Muslim societies. Awass’ investigation of fatwas is historically contextualized and he demonstrates legal development through his selection of fatwas. Furthermore, his analysis provides a fascinating window into the minds of renowned Muslim jurists and their engagement with the legal tradition. Finally, while Awass’ main focus is on the Sunnī legal tradition, his inclusion of non-Sunnī sects, Zaydī and Ibāḍī traditions respectively, while informative, could be improved with a stronger comparative context.